1998
DOI: 10.1007/s002210050271
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic consolidation: a third phase of reorganization after peripheral nerve injury in adult squirrel monkeys

Abstract: It has previously been demonstrated that the central somatosensory topographic reorganization within deprived cortex that follows peripheral nerve injury in adult monkeys occurs in at least two stages: an immediate unmasking period; and a more prolonged period where deprived areas of cortex come to express new receptive fields in a topographically arranged manner. In the present experiments, we have compared cortical topography many months after combined median and ulnar nerve transection with "complete" reorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 28 publications
1
38
1
1
Order By: Relevance
“…After restricted SCI in owl monkeys (complete and incomplete dorsal column lesions), extensive remapping has been observed in the hand area of the PoCG, and this reorganization also followed a somatotopic pattern (10). Segregated cortical remapping in the monkey has been reported after deafferentation, but over a smaller scale (Յ5 mm) (7,11,39). The perceptual and cortical reorganization observed in the current study is evidence for extensive and segregated PoCG reorganization, and does not support the hypothesis that takeover of deafferented cortex by adjacent representations in the PoCG is a necessary correlate of phantom sensations.…”
Section: Discussionmentioning
confidence: 99%
“…After restricted SCI in owl monkeys (complete and incomplete dorsal column lesions), extensive remapping has been observed in the hand area of the PoCG, and this reorganization also followed a somatotopic pattern (10). Segregated cortical remapping in the monkey has been reported after deafferentation, but over a smaller scale (Յ5 mm) (7,11,39). The perceptual and cortical reorganization observed in the current study is evidence for extensive and segregated PoCG reorganization, and does not support the hypothesis that takeover of deafferented cortex by adjacent representations in the PoCG is a necessary correlate of phantom sensations.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are surprisingly rapid. Both human and primate studies have reported that changes in cortical activity take place within the first few weeks following injury (Merzenich et al, 1983;Mogilner et al, 1993) and that chronic changes begin within the first two months (Churchill, Muja, Myers, Besheer, & Garraghty, 1998). These changes take place in several forms including alteration of normal inhibition/excitation processes, atrophy of normal structures and formation of new connections .…”
Section: Changes Within the Central Nervous Systemmentioning
confidence: 99%
“…AVerent regulation is crucial for the maintenance and survival of post-synaptic neurons in the somatosensory (Dietrich et al, 1985;Churchill et al, 1998;Xu and Wall, 1999;Jain et al, 2000;Woods et al, 2000), visual (LeVay et al, 1980;Wong-Riley and Carroll, 1984;JeVery and Parnavelas, 1987;Chino et al, 1992;Chino, 1995;Yinon et al, 1995;Horton and Hocking, 1998), olfactory (Westrum and Bakay, 1986;Capurso et al, 1997;Leung and Wilson, 2003;Mandairon et al, 2003), and auditory (Born and Rubel, 1985;Pasic and Rubel, 1989;Rubel et al, 1990;Born et al, 1991;Lippe, 1991;Pasic and Rubel, 1991;Sie and Rubel, 1992;Edmonds et al, 1999;Mostafapour et al, 2000) systems of mammals and avians.…”
Section: Introductionmentioning
confidence: 99%